Roots of our people: Fruit trees and their custodians in Kyrgyzstan and Tajikistan - Oudenhoven, F. van; Bioversity International (2011)
Some of the world’s most important fruit species find their origin in the mountains of Central Asia. Over the centuries, nature and man have shaped these fruits into a diversity that has become a mainstay of everyday survival.This booklet presents some of the farmers who are contributing to the conservation of that diversity in Kyrgyzstan and the Tajik Pamirs. It is a tribute to their energy and curiosity, to the stories they tell and the work they do to preserve a uniquely important part of their heritage. It is also a reflection on the nature of custodianship – on what it means, in practice, to care for the earth and one’s community.